Antithrombotic actions of statins involve PECAM-1 signaling - Moraes, Leonardo A. (American Society of Hematology, 2013)
Statins are widely prescribed cholesterol-lowering drugs that are a first-line treatment of coronary artery disease and atherosclerosis, reducing the incidence of thrombotic events such as myocardial infarction and stroke. Statins have been shown to reduce platelet activation, although the mechanism(s) through which this occurs is unclear. Because several of the characteristic effects of statins on platelets are shared with those elicited by the inhibitory platelet adhesion receptor PECAM-1 (platelet endothelial cell adhesion molecule-1), we investigated a potential connection between the influence of statins on platelet function and PECAM-1 signaling. Statins were found to inhibit a range of platelet functional responses and thrombus formation in vitro and in vivo. Notably, these effects of statins on platelet function in vitro and in vivo were diminished in PECAM-1(−/−) platelets. Activation of PECAM-1 signaling results in its tyrosine phosphorylation, the recruitment and activation of tyrosine phosphatase SHP-2, the subsequent binding of phosphoinositol 3-kinase (PI3K), and diminished PI3K signaling. Statins resulted in the stimulation of these events, leading to the inhibition of Akt activation. Together, these data provide evidence for a fundamental role of PECAM-1 in the inhibitory effects of statins on platelet activation, which may explain some of the pleiotropic actions of these drugs.